Penerapan Model Inkuiri Terbimbing Berbantuan Aplikasi Kodular dalam Pembelajaran Sistem Gerak Pada Manusia Untuk Meningkatkan Kemampuan Berpikir Kritis dan Literasi Sains Siswa Kelas XI SMA - Agustina, Rezeki Sri; Sipahutar, Herbert; Diningrat, Diky Setya (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to determine the effect of the application of the guided inquiry model assisted by the Kodular application on students' critical thinking skills and scientific literacy skills, and to understand which influence is greater between the critical thinking skills and scientific literacy skills of students who use the guided inquiry model assisted by the Kodular application on the material of the human locomotor system of class XI SMA. The study was conducted at SMA Negeri 1 Aek Natas with a sample of 2 classes determined by cluster random sampling technique, namely the experimental class of 35 students and the control class of 34 students. The research data were collected using test instruments consisting of a critical thinking ability test (30 multiple choice questions) and a scientific literacy ability test (5 essay questions). The data were analyzed using an independent sample t-test approach with the help of the SPSS program. The results of the study showed that: (1) the application of the guided inquiry model assisted by the Kodular application had a significant effect on students' critical thinking skills (p = 0.001); (2) the application of the guided inquiry model assisted by the Kodular application had an effect on students' scientific literacy skills (p = 0.013); and (3) the application of the guided inquiry model assisted by the Kodular application has a greater influence on students' critical thinking skills compared to students' scientific literacy skills in learning about the human movement system in class XI of SMA Negeri 1 Aek Natas (p=0.000).